Development of creative tourism with emphasis on tourism attractions (Case Study: Isfahan City) - M. Taghvaei; Sheida Janali poor; Marjan Shafiei (نشریه جغرافیا و برنامه‌ریزی, 2022)
IntroductionIn 2016, almost 55% of the world’s population were living in cities which is anticipated to amount to 66% by 2050. As the population grows, competition between cities as tourism destinations also grows (Boivin & Tanguay, 2019:67). Tourism is a major industry globally, with so many people spending their time in recreation and travel each year (Taghvaei & Jozi-Khamsalouei, 2016:163). This rapidly growing industry which is affecting economies considerably (Bazrafshan & Bameri, 2018:168), is becoming one of the main components of the world’s trade shortly (Taghvaei & Hosseini-Khah, 2017:9). Today, tourists seek to gain more interactive and satisfying experiences, as creative tourism can be an effective way to connect this (Mohammadi et al. 2016:5). Creative tourism is gaining momentum and seeks to provide modern tourism development strategies (Kiani Salmi & Safari, 2017:117). Creative tourism paves the way for societies to achieve development (Saniei et al. 2014:84). With an oil-dependent economy, Iran has not done non-oil economy and revenue generation through other channels; thus, it should seriously engage in tourism (Taghvaei et al. 2013:172) because it enjoys the potential to become a strong tourism hub.Meanwhile, creative tourism refers to a more developed form of tourism that has a rich historical and cultural background in Iran, especially in Isfahan (Shafie et al. 2014:251), which enjoys nationally and internationally-recognized attractions and draws many tourists from all over Iran and the world (Taghvaei & Izadi, 2012:32). Therefore, given the positive outcomes that tourism may bring about for cities and also the role of the city of Isfahan as a tourism city, the present research investigates the most important components affecting the creative tourism development in Isfahan and emphasizes tourism attractions. It also seeks to answer the following questions: What is the distribution of tourism attractions in Isfahan? AndWhat are the most important components affecting the development of creative tourism in Isfahan?Data and MethodThe present research falls under applied-developmental studies in terms of goals and uses a descriptive-analytical method from a methodological perspective. Data required were gathered from library and document sources and field surveys. A research questionnaire was developed using indicators extracted from books, scientific articles, views, and related theories in creative tourism, including four dimensions and 29 indicators. Also, factorial analysis, the Analytic Hierarchy Process (AHP) (TOPSIS and SAW), Partially Ordered Set (POSET) methods, and entropy coefficient were used to analyze the data.According to Isfahan’s Handicraft and Tourism Organization, the statistical population was 850000 in 2018. The Cochran formula yielded a total sample size of 385 tourists and officials working in the tourism sector (Cultural Heritage, Handicrafts and Tourism Organization) selected via the snowball sampling method.Results and DiscussionFactor analysis model findings suggest that social-cultural (9 variables), artistic-cultural (6 variables), structural-institutional (7 variables), and finally economic (6 variables) factors were the most important factors affecting the materialization of creative tourism in the city of Isfahan, which could explain 49.73% of the total variance. AHP, TOPSIS and SAW methods were used to prioritize the indicators. Also, the POSET method was used to rank the indicators.Model findings of the cultural dimension suggest that the criterion of official attention to the cultural heritage, learning experiences and new skills and holding handicraft industries workshops are ranked first to third, respectively. Model finding of the structural dimension also suggests that creativity in design, standard location and quality of tourism infrastructure, and the effects of night transportation on the use of tourism attractions take first to third ranks, respectively. The prioritization of social dimension indicators reveals that the sub-criterion of security and peace of mind in tourism spaces, greater interaction between people and tourists and holding sports-cultural games take first to third priorities. As regards the economic dimension, components of handicrafts industries marketing, appropriate distribution of sale centers and diversity of tourism services consistent with all income groups are ranked first to third. In the meantime, the entropy coefficient for the distribution of attractions in the city of Isfahan was 0.5, which indicates a greater concentration and imbalanced distribution of the attractions in the municipal districts of the city.  It is thus required to develop and balance new attractions fundamentally.ConclusionWith so many historical sites, the metropolis of Isfahan is considered one of the most popular tourist hubs in Iran, which necessitates tourism planning for this city. The distribution of tourism attractions in Isfahan indicates greater concentration and imbalanced distribution of the attractions in municipal areas of the city. Despite the large number of tourists flowing into this city, their presence is limited to some areas, with people of Isfahan themselves having to travel longer distances to see the attractions. Thus, one of the critical solutions is to employ successfully implemented models and ideas for creating new attractions in areas which lack attractions. Also, to materialize creative tourism in Isfahan, it is imperative to provide planning on major components and indicators and understand and prioritize these indicators so that creative tourism is developed and implemented.